A new species of the genus Austinogebia Ngoc-Ho, 2001 (Crustacea, Decapoda, Gebiidea, Upogebiidae) from northern China - Liu, Wenliang; Liu, Ruiyu (Zootaxa, 2012)
A new species of the genus Austinogebia Ngoc-Ho, 2001, A. monospina n. sp., collected from the Bohai Sea and theYellow Sea, is described and illustrated. It is closely allied to A. spinifrons (Haswell, 1881) but differs markedly in the rostral ornamentation, with one infrarostral spine and the unarmed lower margin of antennal peduncle.